Inflation and Banking Liquidity Effects on GDP Growth in Russia - Karimov Ibrohimbek Vohid Oglu; Saydullayev Azamat; Elbekov Beksultan Ikhtiyorjon Oglu; Ismailov Sardorbek Shukhratovich; Ilmuratov Kamoliddin Mukhiddin Oglu (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Economic growth is a central indicator of national performance, with inflation and banking liquidity recognized as key macroeconomic variables shaping monetary conditions and financial intermediation. Specific Background: In transition economies such as Russia, fluctuations in inflation and banking sector liquidity have been closely associated with variations in GDP growth over recent decades. Knowledge Gap: Prior studies have largely examined inflation and growth separately, while the combined relationship between inflation, banking liquidity, and economic growth remains underexplored, particularly in the Russian context. Aims: This study aims to empirically examine the relationship between inflation, banking sector liquidity, and GDP growth in Russia using annual data from 2000 to 2024. Results: The findings from OLS and robust regression indicate that inflation demonstrates a positive and statistically significant association with GDP growth, while banking liquidity shows a weaker but still statistically relevant relationship. Logarithmic transformations further improve model accuracy and reveal consistent patterns across specifications. Novelty: This study considers inflation and banking liquidity jointly as an interactive macroeconomic phenomenon and applies logarithmic transformations to address uncertainty and heteroscedasticity. Implications: The results suggest that maintaining controlled inflation is associated with sustained economic growth, while banking liquidity plays a complementary role in supporting financial stability and economic activity within monetary policy frameworks. Highlights: • Inflation exhibits a statistically significant positive relationship with GDP expansion• Banking sector liquidity shows a modest yet meaningful association with growth dynamics• Logarithmic model specification provides higher explanatory accuracy for macroeconomic relationships Keywords: Inflation, Banking Liquidity, GDP Growth, Monetary Policy, Transition Economies